Hydrography, nutrients and plankton abundance in the hot spot of Abu Qir Bay, Alexandria, Egypt - ABDEL-AZIZ, N.E.; FAHMY, M.A.; DORGHAM, M.M. (Mediterranean Marine Science, 2001)
The hydrography, nutrient levels and plankton abundance were investigated monthly for a complete annual cycle in the southwestern part of Abu Qir Bay, the most polluted and biologically productive area on the Egyptian Mediterranean coast. Intense temporal and spatial variability was observed in all measured parameters characteristic of the effects of several effluents discharged into the bay. Based on the present investigation, the southwestern Bay can be divided ecologically and biologically into two parts: one including the near shore strip, which is directly affected by the waste waters, and a second comprising the southwestern part of the coastal strip and the offshore stations, both of which are relatively far away from the land-based effluents. The Bay water was characterized by low transparency (monthly average: 64-280 cm), dissolved oxygen (monthly average 2.0-6.8 mg/l) and surface salinity (monthly average: 24.8-37.9 ppt), the highest limits usually being in the offshore section. Water fertility and plankton production were high in the Bay indicating an occasionally acute degree of eutrophication, particularly nearshore. Great variations occurred in the concentrations of nutrients throughout the year, with monthly averages of 0.8-50.88 mM for ammonia, 0.42-3.28 mM for nitrite, 1.29-17.36 mM for nitrate, 0.32-3.61 mM for reactive phosphate and 1.09-33.34 mM for reactive silicate. Similarly, the abundance of both phytoplankton and zooplankton showed pronounced temporal and spatial variability, whereas the monthly average chlorophyll-a fluctuated between 2.06 and 52.64 mg/l and zooplankton between 31x103 and 248.6x103 ind./m3. However, the absolute values of all parameters indicated remarkably wider ranges of variations. Significant correlation was found between chlorophyll-a and some ecological parameters like temperature, salinity, transparency, dissolved oxygen, nitrite and between zooplankton and temperature, while there was a significant correlation between nutrient concentrations and salinity changes.